The CHLI1 Subunit of Arabidopsis thaliana Magnesium Chelatase Is a Target Protein of the Chloroplast Thioredoxin - Ikegami, Akinori; Yoshimura, Naho; Motohashi, Ken; Takahashi, Shigekazu; Romano, Patrick G.N.; Hisabori, Toru; Takamiya, Ken-ichiro; Masuda, Tatsuru (The Journal of biological chemistry, 2007)
Insertion of magnesium into protoporphyrin IX by magnesium chelatase is a key step in the chlorophyll biosynthetic pathway, which takes place in plant chloroplasts. ATP hydrolysis by the CHLI subunit of magnesium chelatase is an essential component of this reaction, and the activity of this enzyme is a primary determinant of the rate of magnesium insertion into the chlorophyll molecule (tetrapyrrole ring). Higher plant CHLI contains highly conserved cysteine residues and was recently identified as a candidate protein in a proteomic screen of thioredoxin target proteins (Balmer, Y., Koller, A., del Val, G., Manieri, W., Schurmann, P., and Buchanan, B. B. (2003) Proc. Natl. Acad. Sci. U. S. A. 100, 370–375). To study the thioredoxin-dependent regulation of magnesium chelatase, we first investigated the effect of thioredoxin on the ATPase activity of CHLI1, a major isoform of CHLI in Arabidopsis thaliana. The ATPase activity of recombinant CHLI1 was found to be fully inactivated by oxidation and easily recovered by thioredoxin-assisted reduction, suggesting that CHLI1 is a target protein of thioredoxin. Moreover, we identified one crucial disulfide bond located in the C-terminal helical domain of CHLI1 protein, which may regulate the binding of the nucleotide to the N-terminal catalytic domain. The redox state of CHLI was also found to alter in a light-dependent manner in vivo. Moreover, we successfully observed stimulation of the magnesium chelatase activity in isolated chloroplasts by reduction. Our findings strongly suggest that chlorophyll biosynthesis is subject to chloroplast biogenesis regulation networks to coordinate them with the photosynthetic pathways in chloroplasts.